An atlas of gross and histologic lesions and immunohistochemical immunoreactivity during the temporal progression of aerosolized Lassa virus induced hemorrhagic fever in cynomolgus macaques - Bohler, Forrest; Cashman, Kathleen; Wilkinson, Eric; Johnson, Joshua C.; Rosenke, Kyle; Shamblin, Josh; Hensley, Lisa; Honko, Anna; Shaia, Carl (Frontiers in Cellular and Infection Microbiology, 2024)
Lassa virus (LASV) causes an acute multisystemic hemorrhagic fever in humans known as Lassa fever, which is endemic in several African countries. This manuscript focuses on the progression of disease in cynomolgus macaques challenged with aerosolized LASV and serially sampled for the development and progression of gross and histopathologic lesions. Gross lesions were first noted in tissues on day 6 and persisted throughout day 12. Viremia and histologic lesions were first noted on day 6 commencing with the pulmonary system and hemolymphatic system and progressing at later time points to include all systems. Immunoreactivity to LASV antigen was first observed in the lungs of one macaque on day 3 and appeared localized to macrophages with an increase at later time points to include immunoreactivity in all organ systems. Additionally, this manuscript will serve as a detailed atlas of histopathologic lesions and disease progression for comparison to other animal models of aerosolized Arenaviral disease.